CdS quantum dots: enzyme mediated in vitro synthesis, characterization and conjugation with plant lectins - Ansary, Abu Ayoobul; Kumar, S. Anil; Krishnasastry, M. V.; Abyaneh, Majid Kazemian; Kulkarni, Sulabha K.; Ahmad, Absar; Khan, Mohammad Islam (Journal of Biomedical Nanotechnology, 2007)
This paper presents the in vitro synthesis of CdS quantum dot nanoparticles using sulphite reductase and capping peptide in the presence of a co-factor alpha-NADPH, their characterization and conjugation with plant lectins, Jacalin and Chick pea lectin. Incubation of sulphite reductase with aqueous CdCl2, Na2SO3, and capping peptide in the presence of a-NADPH, which acts as a co-factor, resulted in the formation of CdS nanoparticles of dimensions 5-20 nm. These CdS nanoparticles were conjugated with plant lectins by EDAC mediated coupling. These observations are of significance, as it will help in the development of eco-friendly process for the formation of CdS nanoparticles and their application as fluorescent biolabels. Moreover the above studies will also help in designing a rational enzymatic strategy for the synthesis of nanomaterials of different chemical composition, shapes and sizes as well as their separation.
Keywords: bio-label; CdS quantum dots; conjugation; Enzyme; in vitro synthesis; Nanoparticles